Determining The Commodities and Primary Areas of The Plantation Crop Subsector in The Meranti Islands Regency - Harmaidi, Desma; Yasid, Hamdan; Siswati, Latifa (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: To enhance a region's economy, it is essential to implement a development strategy focused on key sectors. This includes identifying and leveraging the potential of the plantation crop subsector to create competitive, high-value agricultural activities that can increase regional income. Purpose: This study aims to identify the key commodities and areas within each plantation crop subsector in Meranti Islands Regency, Riau Province. Design/methodology/approach: It utilizes five years of production data (2017-2021) from the Central Bureau of Statistics of Meranti Islands Regency. Analytical methods used to identify the superior products of plantation crops include the Sectoral Contribution Index (IKS), Growth Ratio Model (MRP), Location Quotient (LQ), Dynamic Location Quotient (DLQ), Composite Index (IK) and Hot Spot (Getis-Ord Gi*). Findings/Result: The results indicate that the leading plantation crop commodities in Meranti Islands Regency are sago, coconut, coffee, and areca nut. These commodities are identified as the most promising based on their contribution, growth rate, production capacity to meet regional needs, export potential, and future prospects. The flagship areas are Tebing Tinggi Timur District for sago, Rangsang District for coconut, Rangsang Pesisir District for coffee, and Rangsang Barat District for areca nut. Thus, the government must make a plan for the development of plantations with the potential of each region that can improve the economy of the region.Conclusion: The government must make a plan for the development of plantations with the potential of each region that can improve the economy of the region.Originality/value (State of the art): This study uses GIS for spatial analysis and mapping of land potential based on factors such as soil fertility, rainfall, and topography. Keywords: composite index, featured commodities, featured regions, plantation crop subsector, hot spot (Getis-Ord Gi*)